TANGGUNG JAWAB KEPALA MADRASAH DALAM PERSPEKTIF PENDIDIKAN ISLAM: Kajian Akademik, Moral-Spiritual, dan Sosial - Hamzah Umasugi, M.Pd.I Umasugi; Hasan Pauwah (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This study aims to analyze the responsibilities of madrasah principals across three interrelated dimensions academic, moral-spiritual, and social through the lens of Islamic education. Employing a qualitative library research approach with descriptive-qualitative analysis of indexed scholarly journals, textbooks, and relevant policy documents, the study yields three principal findings. First, systematic and continuous academic supervision is a determinant factor in improving teachers’ pedagogical competence and learning quality. Second, the moral-spiritual exemplarity of madrasah principals directly shapes the formation of an Islamic organizational culture and a conducive work climate. Third, substantive rather than ceremonial community partnerships produce measurable outcomes for institutional legitimacy and sustained educational quality improvement. The study further identifies that low managerial competence among madrasah principals resulting in non-conducive work climates and the scarcity of structured leadership development programs constitute the primary barriers to realizing these responsibilities. The original contribution of this article lies in its cross-dimensional synthesis, integrating Qur’anic and Hadith normative foundations with the EMASLIM management framework into a single cohesive and operational analytical framework for Islamic educational leadership.